The potential impact of an electronic medication management system on safety‐critical prescribing errors in an emergency department. (16th April 2019) - Raban, Magdalena Z.; Walter, Scott R.; Pont, Lisa G.; Cheung, Louis; Strumpman, Dana; Westbrook, Johanna I.
Abstract: Background: Medication errors in hospitals are common. Although electronic medication management systems (eMMS) have the potential to reduce errors during inpatient care, little is known about their effect in emergency departments (ED). Aim: The aims of this study were to report on the types of prescribing errors in an ED prior to implementation of an eMMS, to assess the risk the errors pose to patient safety and to evaluate whether safety‐critical errors were potentially preventable with a newly implemented eMMS. Methods: Medication orders on paper charts were assessed for prescribing errors by a clinical hospital pharmacist. Error severity was rated using a five‐point scale. Errors of moderate or higher severity, and all errors involving defined high‐risk medicines were considered safety‐critical errors. The potential for safety‐critical errors to be prevented by the eMMS was rated (likely, possibly or unlikely). Results: Across 239 medication orders, 208 errors (27 clinical, 181 legal or procedural) were identified. The overall prescribing error rate was 0.87 errors/order. There were 67 safety‐critical errors (53 legal or procedural, 14 clinical). Overall, 82.1% of errors were likely preventable by eMMS. However, of the clinical safety‐critical errors, only 2 (14.3%) were considered likely preventable. Conclusion: Although eMMS has the capacity to prevent a high proportion of safety‐critical legal or procedural errors in the ED, clinical prescribing errors in this category were unlikely to be prevented by using eMMS. Further investigation of these more severe error types could guide the design of eMMS decision support to improve system effectiveness.